Settlements dimensons of community development - Tóth, Tamás (Studia Mundi – Economica, 2018)
The article investigates and systematises the process, tools, and methods that influence and support successful community building. Although involving communities in the planning processes is obligatory for the EU member states, complying with the generally formulated rules of this topic, which is difficult to regulate to begin with, does not mean that a planning process carried out according to rules would actually become community planning in practice. The system of community planning has been investigated and its importance has been proven by many academics, but the most solid basis for community planning models comes from the experience of projects carried out by actual communities. Community planning is a process in which the stakeholders are involved from the very early stages. This kind of involvement in the planning process of the public authorities is increasingly required by national law, planning methodologies and international treaties. For this very reason present study deals with this highly important topic.